Trade, Internal Migration, and Human Capital : Who Gains from India’s IT Boom? - Ghose, Devaki (World Bank, Washington, DC, 2021)
How do trade shocks affect welfare and inequality when human capital is endogenous? Using an external information technology demand shock and detailed internal migration data from India, this paper first documents that both information technology employment and engineering enrollment responded to the rise in information technology exports. Information technology employment responded more when nearby regions had a higher share of college-age population. The paper then develops a quantitative spatial equilibrium model featuring two new channels: higher education choice and differential costs of migrating for college and work. The framework is used to quantify the aggregate and distributional effects of the information technology boom and perform counterfactuals. Without endogenous education, the estimated aggregate welfare gain from the export shock would have been about a third as large and regional inequality twice as large. Reducing barriers to mobility for education, such as reducing in-state quotas for students at higher education institutes, would substantially reduce inequality in the gains from the information technology boom across districts.